Program evaluation of football development in gagak muda football school - Aji Panunggal; Fatah Nurdin; Kurnia Tahki (Gladi : Jurnal Ilmu Keolahragaan, 2023)
The purpose of this study was to determine the results of the evaluation of the football coaching program at the Gagak Muda football school which included the components of context, input, process and product. This research is a type of evaluation research through a quantitative and qualitative approach. Program evaluation is carried out to determine the achievement of the targets that have been set. Then make a decision on the program. In the program evaluation research using the CIPP evaluation model, namely context, input, process, product. The four evaluation aspects are used to determine the implementation. The research subjects in this study were 6 respondents the overall component at the Gagak Muda football school were management, coaches, students and parents.